High purity nano-silica from rice husk ash (RHA) via chemical methodas additive/stabilizing agent for CO2 capture application - Mahmud, Mudrikah Sofia; Mohd Daud, Farah Diana; Sarifuddin, Norshahida; Mohd Zaki, Hafizah Hanim; Nordin, Norhuda Hidayah; Mohammad, Nur Farahiyah (Trans Tech Publications Ltd, 2022)
This paper aims to synthesize high purity nano-sized silica from rice husk ash (RHA) by chemical method and investigate its physical and chemical properties. Through a controlled burning of rice husk, the white-colored RHA is obtained. Next, the RHA is subjected to the pre-treatment of acid leaching and thermal treatment. The synthesizing process has been done through the precipitationmethod. The EDX and FTIR analysis confirmed that the prepared powder consists of high purity silica particles through the detection of characteristic peaks of O and Si elements and the presence of primary bonds in silica, which are silanol groups and siloxane bonds. Meanwhile, the FESEM micrograph shows that silica particles in nano-scale had been obtained with an average diameter of 74.0 nm – 84.0 nm. The XRF and XRD analysis confirmed that the prepared powder yields 99.68% nano-silica in an amorphous structure.